(untitled) (Ibrahim Cardiac Medical Journal, 2016)
Truncus arteriosus communis (TAC) is a rare heart disorder with the prevalence of approximately 1%, mostly in male newborns with congenital heart defect (CHD). In this disease, aorta and pulmonary artery have not separated during fetal development and both originate jointly from a truncal vessel. In addition, various disorders are reported as associations of mitral and tricuspid valve defects, atrial septal defect (ASD), pulmonary hypertension, increase in heart rate and discharge syndrome. Ibrahim Cardiac Med J 2014; 4(2): 68-71